The Effects of Generative AI on High-Skilled Work: Evidence from Three Field Experiments with Software Developers - Cui, Zheyuan (Kevin); Demirer, Mert; Jaffe, Sonia; Musolff, Leon; Peng, Sida; Salz, Tobias (2025)
This study evaluates the impact of generative AI on software developer productivity via randomized controlled trials at Microsoft, Accenture, and an anonymous Fortune 100 company. These field experiments, run by the companies as part of their ordinary course of business, provided a random subset of developers with access to an AI-based coding assistant suggesting intelligent code completions. Though each experiment is noisy, when data is combined across three experiments and 4,867 developers, our analysis reveals a 26.08% increase (SE: 10.3%) in completed tasks among developers using the AI tool. Notably, less experienced developers had higher adoption rates and greater productivity gains.